Earlier anti-TNF therapy reduces the risk of malnutrition associated with alterations in body composition in patients with Crohn’s disease - Wang, Yuexin; Yao, Danhua; He, Yining; He, Qi; Li, Yousheng (Frontiers in Nutrition, 2023)
Background: Anti-TNF therapy has been found to exert an influence on long-term nutritional status and even reverse malnutrition in patients with Crohn’s disease. Aims: to observe the effect of anti-TNF therapy on nutritional status in patients with Crohn’s disease, investigate the correlation between the timing of anti-TNF therapy and the human body composition and examine independent body composition factors for predicting malnutrition in these patients. Methods: This was a retrospective study of 115 patients with Crohn’s disease. Body composition parameters were assessed by bioelectrical impedance analysis. The nutritional status of the patients was determined by NRS2002 and MNA. Results: The BMI, BFMI, FFMI, BCMI, SMI, BMC, intracellular water, protein and BMR were significantly lower in patients without any biologic agents (p<0.05). Negative correlations were found between BMC, intracellular water, extracellular water, protein and BMR and the interval between the first symptom and first dose by Spearman's correlation analysis (r <0, p<0.05). Low BMI (OR 0.602, 95% CI 0.434-0.836, p=0.002), low FFMI (OR 0.678, 95% CI 0.507-0.906, p=0.009), and low BCMI (OR 0.564, 95% CI 0.367-0.868, p=0.009) were independent risk factors for malnutrition in Crohn's disease patients. Anti-TNF therapy tended to reduce the malnutrition probability as assessed by Cox regression analysis (OR: 0.217, 95% CI 0.057-0.821, p=0.024). Conclusion: Body composition analysis is predictive of malnutrition in patients with Crohn's disease. Early application of anti-TNF therapy significantly affected skeletal muscle mass, fat mass and bone mineral content, supporting their long-term nutritional status and reducing their probability of malnutrition.